2002
DOI: 10.1177/001316402236880
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of the MaCandrew Alcoholism Scale

Abstract: Using a meta-analytic approach, the authors examined the predictive validity of scores on the MacAndrew Alcoholism Scale. Across 161 studies involving a total sample of 31,320 individuals, the proportion correct classification was .70. When a cut score of 24 was used across 63 studies involving a total sample of 11,113 individuals, the proportion correct classification was .72. The proportion correct classifications for the different cut scores were cumulated separately, and the functional graph suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Conscientiousness and its facets predict health behaviors, drug use, and mortality (Roberts, Chernyshenko, Stark, & Goldberg, 2005; meta‐analysis: Bogg & Roberts, 2004). Personality measures predict alcoholism (meta‐analysis: Cooper‐Hakim & Viswesvaran, 2002). …”
Section: A Bit Of History—how We Got Herementioning
confidence: 99%
See 1 more Smart Citation
“…Conscientiousness and its facets predict health behaviors, drug use, and mortality (Roberts, Chernyshenko, Stark, & Goldberg, 2005; meta‐analysis: Bogg & Roberts, 2004). Personality measures predict alcoholism (meta‐analysis: Cooper‐Hakim & Viswesvaran, 2002). …”
Section: A Bit Of History—how We Got Herementioning
confidence: 99%
“…Correlations tend to be higher than those for cognitive ability predictors (meta-analysis of only prospective longitudinal studies: Roberts, Kuncel, Shiner, Caspi, & Goldberg, 2007). d Conscientiousness and its facets predict health behaviors, drug use, and mortality (Roberts, Chernyshenko, Stark, & Goldberg, 2005; meta-analysis: Bogg & Roberts, 2004 Viswesvaran, 2002).…”
Section: Personality and Major Life Outcomesmentioning
confidence: 99%
“…Outside of the performance domain, Big Five traits have also been shown to predict job satisfaction (Judge et al, 2002); subjective well-being (Steel, Schmidt, & Shulz, 2008); major life outcomes such as mortality, divorce, and occupational attainment (Roberts, Kuncel, Shiner, Caspi, & Goldberg, 2007); health behaviors and drug use (Bogg & Roberts, 2004;Roberts et al, 2007); and alcoholism (Cooper-Hakim & Viswesvaran, 2002).…”
Section: Historymentioning
confidence: 99%
“…In the current study, cut scores were used because of their prevalence in applied settings. However, the issue of using cut scores to hire from a sample of job candidates has been broached in previous research (e.g., Cooper-Hakim & Viswesvaran, 2002) and the consensus appears to be that the use of continuous measures is generally preferable to using cut scores. The current study found that the compensatory cut score method had a selection rate for minorities that was extremely close to being indicative of adverse impact.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%